High Reflectivity YDH/SiO2 Distributed Bragg Reflector for UV-C Wavelength Regime - Mohd Sharizal Alias; Abdullah A. Alatawi; Wong Kim Chong; Malleswararao Tangi; Jorge A. Holguin-Lerma; Edgars Stegenburgs; Mohammad Khaled Shakfa; Tien Khee Ng; Abdulrahman M. Albadri; Ahmed Y. Alyamani; Boon S. Ooi (IEEE Photonics Journal, 2018)
A distributed Bragg reflector (DBR) composed of Y2O3-doped HfO2 (YDH)/SiO2 layers with high reflectivity spectrum centered at a wavelength of ∼240 nm is fabricated using radio-frequency magnetron sputtering. Before the DBR deposition, optical properties for a single layer of YDH, SiO2, and HfO2 thin films were studied using spectroscopic ellipsometry and spectrophotometry. To investigate the performance of YDH as a material for the high refractive index layer in the DBR, a comparison of its optical properties was made with HfO2 thin films. Due to larger optical bandgap, the YDH thin films demonstrated higher transparency, lower extinction coefficient, and lower absorption coefficient in the UV-C regime (especially for wavelengths below 250 nm) compared to the HfO2 thin films. The fabricated YDH/SiO2 DBR consisting of 15 periods achieved a reflectivity higher than 99.9% at the wavelength of ∼240 nm with a stopband of ∼50 nm. The high reflectivity and broad stopband of YDH/SiO2 DBRs will enable further advancement of various photonic devices such as vertical-cavity surface-emitting lasers, resonant-cavity light-emitting diodes, and resonant-cavity photodetectors operating in the UV-C wavelength regime.